2014
DOI: 10.1596/1813-9450-6902
|View full text |Cite
|
Sign up to set email alerts
|

Financial (Dis-)Information: Evidence from an Audit Study in Mexico

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
3
19
0
2
Order By: Relevance
“…The results and experiences of the MC methodology with adults and in the business sector [5–8] are similar to the results of our review regarding adolescents in the health sector, and thus add support to the value of this method. For example, in an evaluation study by Friedman et al, MCs were trained to assess provider practices and evaluate the use of mobile phone messages to pharmacists to improve the treatment of childhood diarrhoea in Ghana [49].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The results and experiences of the MC methodology with adults and in the business sector [5–8] are similar to the results of our review regarding adolescents in the health sector, and thus add support to the value of this method. For example, in an evaluation study by Friedman et al, MCs were trained to assess provider practices and evaluate the use of mobile phone messages to pharmacists to improve the treatment of childhood diarrhoea in Ghana [49].…”
Section: Discussionsupporting
confidence: 80%
“…The study found disparities between actual practices of the providers and their self-reported practices. Outside the field of health, the MC method has evaluated the quality and quantity of information provided by the staff of financial institutions in Ghana, Mexico, and Peru [8]. The study found that clients were not offered enough information to compare credit and savings products [8], similar to the result in which we found that adolescents were not offered enough information to compare contraception methods [17].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In a series of recent studies, Ru and Schoar (2016) found that card issuers target less-educated customers by using rewards programs to screen for behavioral biases, while Ponce et al (2017) concluded that Brazilian banks take advantage of households' failure to borrow from low-interest credit cards. In addition, field evidence suggests employees of financial institutions provide little information about avoidable fees, especially to less knowledgeable individuals (Giné et al, 2014).…”
Section: Rent Extractionmentioning
confidence: 99%